Pemberdayaan Masyarakat Miskin Melalui Program Usaha Ekonomi Desa-Simpan Pinjam (UED-SP) - Rusli, Zaili; Yuliani, Febri; Sulistianingsih, Endang; ', Adianto; Sadad, Abdul (Jurnal Kebijakan Publik, 2012)
The purpose of this study to identify and analyze the empowerment of the poor throughprograms UED-SP in Kuala Terusan, District Kerinci, Pelalawan, Riau Province. The researchmethod used is descriptive survey approach, at research that seeks to tell the existing problem-solving that comes with the existing literature. Data collection techniques performed in researchthis in three ways, namely interviews, written sources (documentation), fitted with a questionnaire.The results showed the performance management program UED-SP judged by the public, especiallythe beneficiaries of the program are considered good.